The Edges of Home Ownership - Wood, G.; Smith, S.; Ong, Rachel; Melek, C. (Australian Housing and Urban Research Institute, 2013)
The project aims to describe the circumstances and identify the characteristics of the neglected group of households that churn in and out of ownership; to identify the characteristics and events that drive household decisions at the edges of ownership; to document the contribution of the edges of ownership to the resilience of Australian housing markets.